AGAMA: KERANGKA ETIS PENGEMBANGAN SAINS DAN (BIO) TEKNOLOGI - Boy, Pradana (Jurnal Bestari, 2001)
The progress of modern science and technology has brought serious problems for the mankind life. One of that problem is how to accelerate between the progress of science and technology with the religious value that will not change eternally. So, one of the way to accelerate this two sides is to make an ethical framework for the science and technology progress. The religion, according to this article, is an ethical reference of it. In another words, the progress of science and technology may not against the religious norms and values. In some cases, its progress has brought the human-kind into a deep dangers and destructions. Thus, to overcome them, there are some ethical frameworks and references must be implemented. This article will explain more about